Enhancing Ionic Conductivity of Carboxymethyl Cellulose-Lithium Perchlorate with Crosslinked Citric Acid as Solid Polymer Electrolytes for Lithium Polymer Batteries - Akhiruddin Maddu; Ahmad Sofyan Sulaeman; Setyanto Tri Wahyudi; Abdulloh Rifai (International Journal of Renewable Energy Development, 2022)
Lithium batteries development are triggered so many efforts in producing electronic devices due to its excellent performance as energy storage systems. One of the appealing points solid polymer electrolytes for developing solid-state lithium batteries. In this study, Solid polymer electrolytes with crosslinked treatment (SPE-C) were prepared from carboxymethyl cellulose-lithium perchlorate (CMC-LiClO4) and citric acid (CA) as a crosslinker via solution casting method. All SPE-C membranes were assembled into lithium battery coin cells. Degree of crosslinked and degradation were measured to observe crosslink formation in SPE-C membranes and confirmed by fourier transform infrared (FTIR), whereas SPE-C in coin cells were characterized by electrochemical impedance spectroscopy (EIS) and linear sweep voltammograms (LSV). The results showed that crosslinked process is successfully obtained with C=O from ester linkage of CA vibration within COO- of CMC for the crosslinking bond formation. The crosslink effect also contributed on enhancing ionic conductivities of SPE-C in coin cells from EIS results. The highest ionic conductivity was obtained in SPE-C2 (1.24×10-7 S/cm) and electrochemically stable in 2.15 V based on LSV measurement. SPE-C2 has good dielectric behavior than the others due to the high ions mobilities for migration process from ion clusters formation, thus it would be useful for further study in obtaining the powerful solid-state lithium polymer batteries.